Incumbency Factor, Internal Party Democracy and Democratic Consolidation in Nigeria’s Fourth Republic (Journal of Governance and Development (JGD), 2023)
The objective of this paper is to interrogate the nexus between incumbencyfactor, internal party democracy and democratic consolidation in Nigeria’sFourth Republic. Abundance evidence suggest that Incumbency factor andinternal party democracy exercise monumental influence on the growth ofdemocracy in Nigeria.The paper adopts a conceptual and qualitative methodology. The researchercollected the data through the secondary sources. Thus, relevant materialsincluding textbooks, journal articles, party constitutions and the 1999constitution of Nigeria were consulted in the quest to establish the linkages.The assertion was substantiated and buttressed by the data. The researchunveiled that abuse of incumbency advantage and lack of internal partydemocracy constitute major drawbacks to democratic consolidation inNigeria.Adducing convincing evidence, the paper established `the relationship betweenincumbency factor, internal party democracy and democratic consolidationin Nigeria. The paper is particularly imperative for stakeholders in Nigeria’sdemocratic experience as it would make them to be conscious and refrainfrom abuse of incumbency and adhere to the doctrines of internal partydemocracy in order to fast track democratic growth and consolidation inNigeria.